Educational Choices and Educational Constraints : Evidence From Bolivia - Inchauste, Gabriela (IMF Working Papers; Working Paper, 2000)
Recent efforts at poverty alleviation emphasize increasing government spending on education. However, even if spending were perfectly targeted, it is not evident that spending by itself will lead to higher educational attainment. Bolivian household data is used in this paper to ascertain the probability of an individual quitting school due to financial or other reasons. Simulations show that government cash transfers can help to improve educational attainment somewhat. However, nonmonetary limitations must also be addressed if educational attainment is to improve significantly, in particular, for indigenous women who have the lowest levels of education in the country.